Treatment of periodontal disease in pregnancy for the prevention of adverse pregnancy outcomes: a systematic review of systematic reviews - Sajjad Khan, Najia; Craven, Rebecca; Rafiq, Ayesha; Rafiq, Anam (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the systematic reviews and meta-analyses investigating whether or not periodontal treatment in pregnancy was effective in reducing the adverse pregnancy outcomes of preterm birth, low birth weight, preterm low birth weight, stillbirth, foetal growth restriction, and pre-eclampsia. Method: The umbrella review was conducted on May 30, 2021, and comprised search of electronic databases MEDLINE, EMBASE, Cochrane Database of Systematic Reviews via Ovid and CINAHL via EBSCO for all systematic reviews and meta-analyses, regardless of the publication date, of randomised controlled trials which investigated the effects of periodontal treatment during pregnancy in preventing or reducing the frequency of at least one adverse pregnancy outcome. The selected studies were subjected to quality assessment and narrative synthesis. Results: Of the 110 studies found, 17(15.5%) met the inclusion criteria. Of them, quality assessment was high for 1(5.9%), moderate 14(82.3%), and low 2(11.8%). A total of 8(47%) studies demonstrated an association with low birth weight, 7(41.2%) with preterm birth, 3(17.6%) with preterm low birth weight, 1(5.9%) with small for gestational age, and 1(5.9%) with stillbirth, while no study demonstrated any association with pre-eclampsia. Conclusion: Differential findings provided unclear evidence, but periodontal therapy in pregnancy is still recommended as it causes no harm and reduces the bacterial burden in periodontal disease. Key Words: Periodontal diseases, Infant, Low birth weight, Premature birth, Foetal growth retardation, Stillbirth, Pre-eclampsia.